BIRTH OF SAINT PETERSBURG AGGLOMERATION UNDER THE RULE OF PETER THE GREAT IN 1703–1724 - V. Sementsov, Sergey; A. Akulova, Nadezhda (Gênero & Direito, 2020)
Relevance of this paper’s subject is due to the necessity to elaborate a modern program of the development of Saint Petersburg agglomeration in northwest Russia for the following 15–20 years (up to the 2030s) based on the historical and genetical features of its origin and development. The aim of the paper was to study the early stage of the uprising of the initially urban (and subsequently metropolitan) Saint Petersburg agglomeration in the 1703–1720s on the basis of the drastic functional alterations of the rural resettlement scheme that had existed here over the centuries. The main approach to the problem was a comprehensive city-planning, functional and landscape analysis based on the examination of historical cartography and archival documents. Principal study results include the findings that a purposeful deliberate creation of the ‘’regular” metropolitan Saint Petersburg agglomeration on the orders of Peter the Great was conducted on the basis of the already existed rural resettlement scheme merging historically Russian territories and, partly, newly conquered in 1702–1709). In the 1703–1720s it went through three phases of the primary formation, and spatial development of the governorate and agglomeration outpaced emergence and crystallization of their single center. Future single center of the agglomeration and the center of the governorate, Saint Petersburg, developed with a chronological gap with the territories development. Thus, in the case of Saint Petersburg agglomeration, first of all territories, their nodes and routes were formed by the administrative order, and only afterwards the center was formed which integrated them. This variant of the governorate, agglomeration and their center formation is unconventional for the history of agglomerations development. The data of the article may be useful for both city-planning historians and modern urban specialists.